Fractional-order active fault-tolerant force-position controller design for the legged robots using saturated actuator with unknown bias and gain degradation - Farid, Yousef; Majd, Vahid Johari; Ehsani-Seresht, Abbas (Mechanical systems and signal processing, 2018)
•The control of the legged robots under actuator fault and saturation is considered.•A recurrent dynamical model is proposed to obtain the desired optimal contact force.•The chattering phenomena is eliminated by using fractional-order controller.•A robust super twisting fault estimator is proposed to reconstruct the lumped fault.•The stability of the proposed controller is proved by Lyapunov theory.•The theoretical results are evaluated in Matlab/SimMechanics environment. In this paper, a novel fault accommodation strategy is proposed for the legged robots subject to the actuator faults including actuation bias and effective gain degradation as well as the actuator saturation. First, the combined dynamics of two coupled subsystems consisting of the dynamics of the legs subsystem and the body subsystem are developed. Then, the interaction of the robot with the environment is formulated as the contact force optimization problem with equality and inequality constraints. The desired force is obtained by a dynamic model. A robust super twisting fault estimator is proposed to precisely estimate the defective torque amplitude of the faulty actuator in finite time. Defining a novel fractional sliding surface, a fractional nonsingular terminal sliding mode control law is developed. Moreover, by introducing a suitable auxiliary system and using its state vector in the designed controller, the proposed fault-tolerant control (FTC) scheme guarantees the finite-time stability of the closed-loop control system. The robustness and finite-time convergence of the proposed control law is established using the Lyapunov stability theory. Finally, numerical simulations are performed on a quadruped robot to demonstrate the stable walking of the robot with and without actuator faults, and actuator saturation constraints, and the results are compared to results with an integer order fault-tolerant controller.